Increased Toxicity Risk from Nanoparticulate System in Food and Drug Applications - Hazrina, Aghnia; Muhaimin, Muhaimin; Chaerunisaa, Anis Yohana; Husni, Patihul; Wardhana, Yoga Windhu (Indonesian Food Science and Technology Journal, 2025)
Abstract— Nanotechnology involves manipulating matter at the atomic and molecular levels, leading to the creation of new materials for food and drug application with properties that are not always easily anticipated based on existing knowledge. Among the nearly infinite variety of these substances, some are toxic to biological systems, others are generally harmless, and yet others confer health advantages. The biocompatibility and distribution of these materials must be assessed prior to their use in biological and environmental. Consequently, it is essential to comprehend the toxicity of nanomaterials. Mechanisms of cellular uptake and nanoparticles dispersion in biological settings depend on their physicochemical properties. The pathways in which exposure to nanoparticles is harmful to health are through oxidative stress and inflammation. Recent research have indicated that nanoparticles may cause major health impacts when ingested, inhaled, or applied to the skin without precaution. The main sources of toxicity in nanomaterials include their size, shape, concentration, aspect ratio, crystallinity, surface charge, dissolution, and agglomeration. This review article aims to comprehensively summarize the toxicity aspects of nanoparticles for food and drug application, including physiochemical properties, mechanisms of nanoparticle toxicity, and the health risks, so as to provide an overview for future researchers to develop nanoparticulate in a safer way.